Respostas

2014-05-21T22:46:11-03:00
Escreva, na forma reduzida, os seguintes polinômios
a)8a+5b-6a+b =

8a + 5b - 6a + b =
8a - 6a + 5b + b =
  2a      +    6b   =  por em evidencia
      2a + 6b=
     2(a + 3b)


 
c)6x+3x2-4x+x²-2x=

6x + 3x² - 4x + x² - 2x =
6x - 4x - 2x  + 3x² +x² =
6x - 6x + 4x² =
     0x + 4x²=
 4x(0   + x)=


c)y²-4y+2y²-y+4y=

y² - 4y + 2y² - y + 4y =
y² + 2y² -4y + 4y =
  3y²    - 0y
3y(y - 0) =


d)3xy-2x+5y-4xy+2x-6y=

3xy - 2x + 5y - 4xy + 2x - 6y =
3xy - 4xy - 2x + 2x + 5y - 6y =

   -1xy  - 0x - y =
1y(-x - 1 )=